ANALISIS KINERJA WEBSITE PARAMA PELINDO MENGGUNAKAN PINGDOM TOOLS DAN PAGESPEED INSIGHTS - Nurul Qalbi Haeruddin; Muhammad Rahmat Faizal; Suardi Hi Baharuddin (PROGRESS, 2023)
This study analyzes the performance of a website for one of the companies, namely PARAMA Pelindo, using Pingdom Tools and PageSpeed Insights. This research aims to improve the performance of the PARAMA website in order to improve user experience. The results of the PARAMA website performance analysis show certain things that need to be improved in testing using pingdom tools and PageSpeed Insights. This research contributes to understanding the importance of analyzing the performance of a website and provides practical recommendations for web developers in improving website performance in general.